Calculation of Impurity Levels in SIR 3CV Type Rubber and Mass Balance at the Drying Station in PT. XYZ North Sumatera - Tarigan, Ratna Kristina; Simatupang, Dimas Frananta (International Journal of Applied Research and Sustainable Sciences, 2024)
The quality of latex significantly affects the quality level of rubber produced, with one of its parameters being the impurity level, with a standard value of 0.03%. The impurity level strongly influences the rubber quality, where higher impurity levels correspond to lower rubber quality, and vice versa. The research method employed was experimental and calculation using mass balance. The calculated results indicated impurity levels in the rubber as follows: 0.0059%, 0.0069%, 0.0074%, 0.0419%, 0.0054%, 0.0429%, and 0.0444%. The average total impurity level was 0.0219%. However, some rubber samples did not meet quality standards due to contaminated tapping equipment, inadequate washing processes, and damaged filtration tools. In the mass balance at the drying station, the first input material was 125 kg/hour with a water component balance of 50%, HAS (Hevea Acidic Solution) 12%, SMBS (Sodium Metabisulfite) 8%, and latex 30%. The second input material is 18.75 kg/hour, consisting of 100% steam. The output material at the drying station is 143.75 kg/hour, with a water component balance of 43.47%, HAS 10.43%, SMBS 6.95%, latex 26.08%, and steam 13.07%.